Use of a Vaginal Ring Containing Dapivirine for HIV-1 Prevention in Women. Issue 8 (August 2016) - Baeten, Jared M.; Palanee-Phillips, Thesla; Brown, Elizabeth R.; Schwartz, Katie; Soto-Torres, Lydia E.; Govender, Vaneshree; Mgodi, Nyaradzo M.; Kiweewa, Flavia Matovu; Nair, Gonasagrie; Mhlanga, Felix; Siva, Samantha; Bekker, Linda-Gail; et al.
Abstract : (Abstracted from N Engl J Med 2016; DOI: 10.1056/NEJMoa1506110) The objective of this study was to examine the efficacy of dapivirine vaginal rings in providing protection against human immunodeficiency virus type 1 (HIV-1). HIV-1 infection incidence is one of the highest in sub-Saharan Africa.